Sebaran dan Potensi Keruing (Dipterocarpus spp.) di Pulau Siberut, Sumatera Barat - N. M. Heriyanto; M. Bismark (Buletin Plasma Nutfah, 2014)
Distribution and Potency of Keruing (Dipterocarpus spp.) on the Island of Siberut, West Sumatra. Nur. M. Heriyanto and M. Bismark. Distribution and potency of Dipterocarpus spp. (keruing) were studied in Siberut Biosphere Reserve area, covering Sot Boyak and Bekemen forest village, Siberut National Park, West Sumatra. Six research plots of 50 m x 50 m (0.25 ha) were laid down. The results showed that Dipterocarpus spp. density at the tree level were 31 trees/ha at Sot Boyak and 38 trees/ha at Bekemen forest village with important value index of 63.83% and 77.54% respectively. The strongest association of other trees to Dipterocarpus spp. were Hopea dryobalanoides Miq., Baccaurea bracteata Muell. Arg. and Endospermum diadenum Miq. as reflected respectively by 0.69, 0.67 and 0.56 of Ochiai index. Dipterocarpus spp. were commonly located on the slopes and ridges. The best grouping was on 50-59% Slopes. Slope relationship with the population distribution of Dipterocarpus spp. showed by the equation of Y = 5.83 ln (x) + 3.44 with R2 = 0.90. Regeneration of Dipterocarpus spp. in natural forest is highly dependent on the recruitment population. Saplings recruitment population was 556 individuals/ha, and seedling was 3,434 individual/ha. AbstrakSebaran dan potensi Dipterocarpus spp. (keruing) diteliti di kawasan Cagar Biosfer Siberut yang meliputi hutan Desa Sot Boyak dan Bekemen, Taman Nasional Siberut, Sumatera Barat. Contoh plot penelitian dibuat dengan ukuran 50 m x 50 m (0,25 ha) dengan enam ulangan. Hasil penelitian menunjukkan, kerapatan Dipterocarpus spp. tingkat pohon di hutan Desa Sot Boyak 31 pohon/ha dan Bekemen 38 pohon/ha dengan indeks nilai penting masing-masing 63,8% dan 77,5%. Asosiasi terkuat dengan pohon lain terhadap keberadaan Dipterocarpus spp. adalah Hopea dryobalanoides Miq. indeks Ochiai 0,69, jenis Baccaurea bracteata Muell. Arg. (indeks Ochiai 0,67) dan Endospermum diadenum Miq. (indeks Ochiai 0,56). Habitat Dipterocarpus spp. berada di lereng dan punggung bukit, pengelompokannya terbaik pada kelerengan 50– 59%. Hubungan kemiringan lahan dengan sebaran populasi Dipterocarpus spp. mengikuti persamaan Y = 5,83l n(x) + 3,44 dengan R2 = 0,90. Regenerasi Dipterocarpus spp. di hutan alam sangat bergantung pada populasi anakan. Populasi anakan untuk tingkat belta sebesar di 556 individu/ha, tingkat semai 3.434 individu/ha.